Relationship between Sanitation of Warung Makan Tegal and Intestinal Nematodes Infestations in Cockroaches in Tembalang District, Semarang City - Punguan Sitanggang; Retno Hestiningsih; Martini Martini; Praba Ginandjar (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2018)
Background: Cockroaches are insects that are considered disgusting and act as mechanical vectors. The existence of cockroaches in a place becomes a benchmark of low sanitation in the place. The properties possessed by cockroaches by eating anything, so that in looking for food can spread nematodes by walking and removing dirt on top of food, dishes or other eating utensils that pass. The purpose of this study was to determine the intestinal nematode infestation in cockroaches.Methods: This study was an observational study with a cross sectional approach. The stall samples were taken using a total sampling of 43 stalls and cockroach samples were determined by 2 cockroaches from each warteg.Results: Observations under a microscope showed that intestinal nematodes were found in cockroaches including hookworm (14.0%), and Oxyuris vermicularis (30.2%).Conclusion: Intestinal nematodes (hookworm and Oxyuris vermicularis) are found in cockroach bodies